One Year Experience of the Hand Allotransplantation First Performed after Korea Organ Transplantation Act (KOTA) Amendment - Lee, Nara; Baek, Woo Yeol; Choi, Yun Rak; Joo, Dong Jin; Lee, Won Jai; Hong, Jong Won (Archives of Plastic Surgery, 2023)
The revision of the Korea Organ Transplantation Act (KOTA) in 2018 included hand/arm among the organs that can be transplanted. The first hand transplantation since the revision of KOTA took place in January 2021. A 62-year-old male patient experienced hand amputation on July 13, 2018, by a catapult injury. The patient first visited our institute 3 months after the injury. After serial interviews and an overall evaluation, the patient was registered on the hand transplantation waiting list in January 2020. On January 9, 2021, the patient underwent hand transplantation at the right distal forearm level. The total operation time was 17 hours 15 minutes, and the cold ischemic time was 4 hours 9 minutes. Postoperative immunosuppression was administered based on the protocol used for kidney transplantation. Two acute rejection episodes occurred, on postoperative days 33 and 41. Both rejection episodes were reversible with rescue therapy of a higher tacrolimus trough level, steroid pulse therapy, and topical immunosuppressants. Controlled passive range of motion exercise was started on postoperative day 10. Dynamic splint was applied on postoperative day 18. At 1 year, graft maintenance and functional improvement were satisfactory, and the patient showed a Disabilities of Arm, Shoulder and Hand score of 25.8. We successfully performed the first hand transplantation surgery under the KOTA amendment. It came from the organic and effective cooperation of plastic, orthopaedic, and transplantation departments and we believe it will guarantee the future ongoing success.
Keywords: composite tissue allotransplantation; vascularized composite allografting; hand transplantation